Evaluation of the synergistic effects of epigallocatechin-3-gallate-loaded PEGylated-PLGA nanoparticles with nimodipine against neuronal injury after subarachnoid hemorrhage - Yang, Xianguang; Han, Mengguo; Wang, Xue; Wang, Jian; Sun, Xiaoxue; Zhang, Chunyan; Yan, Shuaiguo; Huang, Liyong; Chen, Ying (Frontiers in Nutrition, 2023)
Subarachnoid hemorrhage (SAH) is a devastating subtype of stroke with high mortality and morbidity. Although serious side effects might occur, nimodipine, a second-generation 1,4-dihydropyridine calcium channel blocker, is clinically used to improve neurological outcome after SAH. Recently, (-)-epigallocatechin-3-gallate (EGCG) has been reported to inhibit Ca2+ overloading-induced mitochondrial dysfunction, oxidative stress, and neuronal cell death after SAH; however, the low bioavailability, instability, and cytotoxicity at a high dose limited the clinical application of EGCG. To overcome these, PEGylated-PLGA EGCG nanoparticles (EGCG-NPs), herein, was constructed to enhance the bioavailability by using the double emulsion method. Antioxidative activity, cytotoxicity, behavioral, and immunohistochemistry studies were carried out to determine the neuroprotective effectiveness after cotreatment with EGCG-NPs (75 mg/kg/d preconditioning for 7 days before SAH) and nimodipine (10 mg/kg/d after 30 min of SAH) by using in vivo SAH models. The optimized EGCG-NPs with Box-Behnken design showed a small particle size of 167 nm, zeta potential of -22.6 mV, encapsulation efficiency of 86%, and a sustained-release profile up to 8 days in vitro. Furthermore, EGCG-NPs (75 mg/kg/d) had superior antioxidative activity than free EGCG (100 mg/kg/d). EGCG-NPs combined with nimodipine exhibited significant synergistic effects against neuronal cell death by suppressing oxidative stress, Ca2+ overloading, mitochondrial dysfunction, and autophagy after SAH. These results suggest that cotreatment with EGCG-NPs and nimodipine may serve as a promising novel strategy for the treatment of SAH.